Valacyclovir in the treatment of acute retinal necrosis - Taylor, Simon RJ (BioMed Central, 2012)
BACKGROUND: To report the outcome of oral valacyclovir as the sole antiviral therapy for patients with acute retinal necrosis (ARN). METHODS: This study reports a retrospective, interventional case series of nine consecutive patients with ten eyes with newly diagnosed ARN treated with oral valacyclovir as the sole antiviral agent. Eight patients received oral valacyclovir 2 g tid (Valtrex, GlaxoSmithKline) and one patient with impaired renal function received oral 1 g tid. The main outcome measures were response to treatment, time to initial response to treatment, time to complete resolution of retinitis, best corrected visual acuity (BCVA) at final follow-up, retinal detachment and development of recurrent or second eye disease. RESULTS: Retinitis resolved in ten of ten (100%) affected eyes. The median time to initial detectable response was seven days and the median time to complete resolution was 21 days. A final BCVA of 20/40 or better was achieved in 6/10 (60%) of eyes. 3/10 eyes (30%) developed a retinal detachment. No patients developed either disease reactivation or second eye involvement over the course of the study (mean follow up 31 weeks, range 7 to 104 weeks). CONCLUSIONS: Treatment with oral valacyclovir as the sole antiviral therapy resulted in complete resolution of retinitis. Final BCVA and retinal detachment rate were comparable with previously reported outcomes for intravenous acyclovir.